SOLUBILITY OF METALLIC MERCURY IN OCTANE, DODECANE AND TOLUENE AT TEMPERATURES BETWEEN 100°C AND 200°C - Miedaner M.M.; Migdisov A.A.; Williams-Jones A.E. (My University, 2005)
The solubility of metallic mercury in dodecane, octane and toluene has been investigated experimentally at temperatures up to 200°C and pressures up to 6 bars (toluene). The equilibrium Hg concentrations are very similar in octane and dodecane, reaching values of 821 ppm and 647 ppm, respectively at 200°C, whereas they are significantly lower in toluene (e.g., 280 ppm at 200°C). The behavior of Hg in toluene is nevertheless similar to that in the alkanes. There is a strong prograde dependence of Hg concentration on temperature in both types of solvent, which can be described by the following experimentally determined relationships: The solubility of metallic mercury can be modeled satisfactorily using a modification of the scaled particle theory designed to predict the behavior of nonpolar solutes in polar solvents. This modification involves an adjustment of the Lennard Jones Potential and the hard-sphere diameters of solute and solvent to account for the effects of temperature.The results of this study suggest that hydrocarbons could play a significant role in transporting Hg in natural systems, which may explain the high concentrations of metallic mercury in some crude oils, as well as the common occurrence of petroleum in epithermal mercury deposits.